TINJAUAN HUKUM TATA NEGARA ISLAM TERHADAP PERAN PEMERINTAH DALAM MENJAGA KETENTERAMAN DAN KETERTIBAN UMUM - Nadya Putri Permata Sari; Saadatul Maghfira (Institut Agama Islam Negeri Batusangkar, 2021)
This study examines the review of Islamic state administration law on the role of government in maintaining peace and public order. The problem is that there are still many violators of peace and order, one of which is a homeless person and a beggar. From this problem the question arises How the Role of the Tanah Datar District Government in Implementing Article 12 of the Tanah Datar District Regulation Number 4 of 2010 concerning Peace and Public Order and How the Legal View of Islamic State Administration against the Role of the Government in the Homeless and Beggars. This research is field research. Data obtained through the interview process conducted with sources related to research. After the data is collected then analyzed by means of qualitative descriptive analysis. this research found that the implementation of Article 12 of Tanah Datar District Regulation Number 4 of 2010 concerning Peace and Public Order by the Tanah Datar District Government related to homelessness and beggars had not been implemented well. This can be seen from the data that there are still many beggars and homeless people who violate the prohibited rules in Article 12 of Tanah Datar District Regulation Number 4 of 2010 concerning Peace and Public Order. The lack of public legal awareness and the unavailability of supporting facilities such as rehabilitation centers are also a factor in the large number of violators of peace and public order regulations. The view of Islamic Constitutional Law on the role of government in the homeless and beggars is the role of the government to carry out amar ma'ruf nahi munkar. The Prophet Muhammad formed the institute of Hisbah. This institution, among others, is tasked with holding control. Judging from the role of the Tanah Datar District Government in implementing Article 12 of the Tanah Datar District Regulation on Homelessness and Beggars, the Tanah Datar District Government has formed an institution tasked with dealing with issues of peace and public order namely the Civil Service Police Unit (SATPOL-PP), this has in accordance with Islamic Constitutional Law.